Why Does Indonesia Have a High Covid-19 Case-Fatality Rate? - Karnadi, Erwin Bramana; Kusumahadi, Teresia Angelia (Universitas Negeri Semarang, 2021)
The COVID-19 pandemic has taken the world by storm, but the magnitude of its impact differs from country to country. As of August 2020, Indonesia’s COVID-19 case-fatality rate is higher than the world average. The aim of our research is to find out why Indonesia has a high COVID-19 case-fatality rate. Using OLS regression models, we found the number of COVID-19 related deaths, the number of COVID-19 tests performed, population age, population, voice and accountability index, and control of corruption index are significant predictors of a country’s COVID-19 case-fatality rate. Based on our results, we conclude that Indonesia’s COVID-19 case-fatality rate is higher than it is supposed to be, mainly because of a lack of COVID-19 testing and accurate public information.